Gaps in Health-Related Quality of Life Among Survivors of Cancer and Cardiovascular Disease: The Korean National Health and Nutrition Examination Survey, 2005 (KNHANES III). (March 2015) - Hwang, In Cheol; Park, Sang Min; Yun, Young Ho; Kim, Kyoung Kon
Few studies performed so far have weighed the health-related quality of life (HRQoL) of cancer survivors against that of cardiovascular disease (CVD) survivors. This study was based on data obtained from the Third Korean National Health and Nutrition Examination Survey. Of adults with available EuroQoL (EQ) information, a total 23 370 individuals (658 CVD survivors, 389 cancer survivors, and 22 323 controls) remained in the final analysis. Cancer survivors have the lowest HRQoL scales among the 3 groups, independent of age. The HRQoL of young cancer survivors was as impaired as that of older cancer survivors, whereas the HRQoL of CVD survivors and controls decreased with increasing age. Cancer survivors also have more problems in all domains of EQ-5D, especially domains of pain/discomfort and anxiety/depression. The study suggests that cancer survivors should receive more intensive attention to develop means of identifying them and to improve their quality of life.